Avaliação do SNP rs12203592 como um biomarcador de gravidade em pacientes com anemia falciforme - Fernandes, Leonardo Peixoto (2024)
Sickle cell anemia's (SCA) main mechanisms are chronic hemolysis and recurrent vaso- occlusion (VOC) crises. Both are responsible for the chronic inflammatory process and systemic endothelial damage. The clinical variability in these patients has a multifactorial cause, being attributed to single nucleotide polymorphisms (SNP). The SNP in the interferon regulatory factor 4 (IRF4) gene has been associated with the inflammatory process in oncohematological diseases. Although many studies have associated IRF4 with various diseases, few have linked this transcription factor to sickle cell anemia. In this context, the study aimed to evaluate the frequency of IRF4 in the rs12203592 region and its association with clinical and laboratory biomarkers in patients with SCA. 98 patients with AF (HbSS) undergoing treatment at the Hematology and Hemotherapy Center of Ceará (HEMOCE) and 79 in the control group (HbAA) were analyzed. Sociodemographic, clinical and laboratory data were collected from medical records, while serum interferon-gamma (IFN-γ) dosage and SNP identification were obtained by Enzyme-Linked Immunosorbent Assay (ELISA) and Real-Time Polymerase Chain Reaction (qPCR), respectively. Data were expressed as mean ± SEM, with *p<0.05. It was observed that 55 (56.2%) of patients with AF lived in the interior of the state. The C/C group presented a higher frequency of 153 (86.4%) in the studied population and no difference was found in the frequency of alleles between patients with SCA and controls. AF patients showed an increase in IFN-γ compared to control. The polymorphic groups (C/T and T/T) had higher levels of direct bilirubin (BD), IFN-γ and reticulocytes compared to the C/C group, as well as lower levels of total hemoglobin and fetal hemoglobin (HbF). The T/T group also showed greater activity of alanine transferase (ALT), aspartate transferase (AST), alkaline phosphatase (FA) and gammaglutamyltransferase (GGT). IFN-γ showed a positive correlation with ALT, AST, FA and GGT and a negative correlation with HbF. Furthermore, HbF also showed a negative correlation with ALT and GGT in patients who do not use hydroxyurea. Uric acid and GGT are influenced by genotype, while urea, lactate dehydrogenase and direct bilirubin are influenced by hydroxyurea (HU). HbF and IFN-γ showed a high area under the curve. The polymorphic group had a higher frequency of hepatomegaly, sickle cell nephropathy and VOC and have a high chance of developing hepatitis, acute chest syndrome (AST), bone necrosis and limb ulcers. Therefore, the T allele is associated with greater susceptibility.